-6(x+5)-3=-33

Simple and best practice solution for -6(x+5)-3=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+5)-3=-33 equation:


Simplifying
-6(x + 5) + -3 = -33

Reorder the terms:
-6(5 + x) + -3 = -33
(5 * -6 + x * -6) + -3 = -33
(-30 + -6x) + -3 = -33

Reorder the terms:
-30 + -3 + -6x = -33

Combine like terms: -30 + -3 = -33
-33 + -6x = -33

Add '33' to each side of the equation.
-33 + 33 + -6x = -33 + 33

Combine like terms: -33 + 33 = 0
0 + -6x = -33 + 33
-6x = -33 + 33

Combine like terms: -33 + 33 = 0
-6x = 0

Solving
-6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 2y^2=-7-3 | | 53.4=2(3.14)r | | 9x^2-24x-20=0 | | 9x^2-24-20=0 | | 81-25x^2=0 | | 2x+5=-9x+4/3 | | 6n^2+22n=0 | | -12x-9=4x^2 | | 2w^2+8w-64=0 | | y=r^2+6r+9 | | y=r^2+r+9 | | 2/9+2/7 | | 1/9*2 | | 4x+3/5=x-4+5 | | 2/7*2 | | 95/151=N/100 | | 4w^2-19=5 | | -0.6=-0.8u+0.6u | | 16x^2-100x+144=0 | | -5p+4=19 | | y=(2x-4)(x+8) | | 113y=4(3y-5) | | .9w+.5w+.1w=-3 | | y=4x^2+39x+27 | | 5v^2+6=17v | | y=1x^2+6x-7+0 | | (8x-9)(5x+3)=0 | | 30x+2y=200 | | 3-1/t^2 | | (-1/t^2)^1/2 | | 7m+mn+14+2n= | | -9+9X-2X^2=X^3-4X^2+X-9 |

Equations solver categories